Gambir, Timber and Coffee: A History of the Trade in Forest and Plantation Products on the East Coast of Sumatra in the 19th Century - Dafisco, Rafli; Wulandari, Serli; Arifin, Nana Fitriana (Regalia Institute, 2024)
The eastern coast of Sumatra has long been integrated into international trade networks. In the 19th century, a number of forest and plantation products—namely gambier, timber, and coffee—emerged as key export commodities. This article aims to identify the trade patterns of gambier, timber, and coffee, and to analyze the dynamics of commerce along the eastern coast of Sumatra during the 19th century. The research employs historical methodology consisting of four stages: heuristic, source criticism, interpretation, and historiography. The findings indicate that gambier, timber, and coffee were significant export goods contributing to the vibrancy of trade in the region. Coffee, in particular, was prioritized by the Dutch colonial administration through the implementation of the cultuurstelsel (forced cultivation system). Furthermore, commercial activity in this area established a linkage between the Sumatran highlands and coastal regions, with the majority of traded commodities originating from the inland territories.